Le' Damas Postre Cafe - Fredo, Aizanirra; Lajukim, Azecquline; Joseph, Eskha Valarie; Zakariah, Nur Hamima Tul Asihkin (2014)
Le' Damas Postre Cafe is a dessert shop located in Hyper mall One Borneo that allows the entire dessert lovers to get their tastes and preferences needs satisfied in one convenient location. Le' Damas Postre cafe serves men, women, and children and provides delivery service. We also allowed customer to share their opinion and suggestion about the taste of our dessert in other to fulfil their wants. There are a lot of shops like us but Le Damas Postre cafe provide better service to entire people whose loves something new because our dessert will be upgrade from time to time by creating a new recipe. Besides that, we also care on those busy and didn't have time by providing delivery service. We Le Damas Postre cafe , saw the opportunity that this business has the potential of success since there is a good care of costumer need based on service provided and delicious taste and preferences of our dessert. Since people tastes and preferences always change, we take care of this by improving our dessert to fix with their wants.